A Survey of Canadian Occupational Therapy Practices to Prevent Pressure Injuries Among Wheelchair Users via Weight Shifting. Issue 3 (May 2018) - Mortenson, W. Ben; Thompson, Sarah C.; Wright, Alison L.; Boily, Jeanette; Waldorf, Kevin; Leznoff, Sandy
Abstract : PURPOSE: The purpose of this study was to describe occupational therapy weight-shifting practices and explore recommended strategies for patients, healthcare staff, and family/caregivers across healthcare settings. DESIGN: Cross-sectional survey. SUBJECTS AND SETTING: Respondents included 97 currently practicing occupational therapists working in 5 main practice settings (ie, acute care, inpatient rehabilitation, outpatient rehabilitation, home and community care, and residential) from 9 out of 10 Canadian provinces. METHODS: We created a 25-item questionnaire that included forced choice and open-ended queries. Items queried demographic information, weight-shifting techniques taught to patients, frequency and duration of weight shifting recommended, educational approaches used to teach weight shifting, and resources used to guide decision making. Participants were recruited via professional organizations and health authorities across Canada. Participants were excluded if they were not currently working with manual or power wheelchair users. Descriptive statistics were used to analyze quantitative data, and content analysis was used for qualitative data (responses to open-ended queries). RESULTS: The most frequently recommended weight-shifting techniques were tilt (83.3%-92.8%), leaning to one side (47.9%-87.5%), and forward leaning (46.9%-83.3%). Study findings revealed a wide range of recommendations regarding frequency (every 10 minutes or less to >2 to 3 hours) and duration (⩽30 seconds to as long as tolerated) of weight shifting. Weight-shifting interventions were most commonly guided by clinical experience (81.7%), practice guidelines (62.4%), and expertise of other team members (54.8%). CONCLUSIONS: Results from this study highlight the need for further research to inform weight-shifting techniques and to build a more comprehensive understanding of weight-shifting education practices.